The correlation between anemia and the incidence of premature rupture of membranes (prom) at regional Public Hospital Panembahan Senopati Bantul - Suciana Indriani; Elika Puspitasari (Universitas 'Aisyiyah Yogyakarta, 2019)
The incidence of premature rupture of membranes ranges from 5-10% of all partum. Preterm PROM occurs in 1% of all pregnancies, 70% of cases occur in term pregnancies and 30% of occurrence of PROM causes of premature birth. This study aimed to determine the correlation between anemia and the incidence of premature rupture of membranes at Regional Public Hospital of Panembahan Senopati Bantul in 2016-2017. The research design was analytic survey method using retrospective time approach. The sample technique used total sampling of 172 mothers with premature rupture of membranes. Based on data analysis it was found that partum women with mild anemia, as many as 155 respondents (90.1%), had premature rupture of membrane PROM 37 weeks, while partum women with moderate anemia, as many as 6 respondents (5.0%), experienced premature rupture of membranes PPROM 37 weeks . Chi Square statistical test results with a significant level of 0.05 obtained p value= 0.001 (p value 0.005). There was a correlation between anemia and the incidence of premature rupture of membranes at Regional Public Hospital of Panembahan Senopati Bantul in 2017. Health workers should provide good ANC services in order to prevent anemia that affects the incidence of premature rupture of membranes.